Endurance training prevents inflammation and apoptosis in hypothalamic neurons of obese mice - Marinho, Rodolfo [UNESP]; Munõz, Vitor R.; Pauli, Luciana S. S.; Ropelle, Eloize C. C.; de Moura, Leandro P. [UNESP]; Moraes, Juliana C.; Moura-Assis, Alexandre; Cintra, Dennys E.; da Silva, Adelino S. R.; Ropelle, Eduardo R.; Pauli, José R. (Wiley, 2018)
This study investigated the effects of exercise training in regulating inflammatory processes, endoplasmic reticulum stress, and apoptosis in hypothalamic neurons of obese mice. Swiss mice were distributed into three groups: Lean mice (Lean), sedentary animals fed a standard diet; obese mice (Obese), sedentary animals fed a high-fat diet (HFD); trained obese mice (T. Obese), animals fed with HFD and concurrently subjected to an endurance training protocol for 8 weeks. In the endurance training protocol, mice ran on a treadmill at 60% of peak workload for 1 hr, 5 days/week for 8 weeks. Twenty-four hours after the last exercise session, the euthanasia was performed. Western blot, quantitative real-time polymerase chain reaction, and terminal deoxynucleotide transferase biotin-dUTP nick end-labeling (TUNEL) techniques were used for the analysis of interest. The results show exercise training increased phosphorylation of leptin signaling pathway proteins (pJAK2/pSTAT3) and reduced the content of tumor necrosis factor α, toll-like receptor 4, suppressor of cytokine signaling 3, protein–tyrosine phosphatase 1B as well as the phosphorylation of IkB kinase in the hypothalamus of T. Obese animals. A reduction of macrophage activation and phosphorylation of eukaryotic initiation factor 2α, and protein kinase RNA-like endoplasmic reticulum kinase (PERK) were also observed in exercised animals. Furthermore, exercise decreased the expression of the proapoptotic protein (PARP1) and increased anti-inflammatory (IL-10) and antiapoptotic (Bcl2) proteins. Using the TUNEL technique, we observed that the exercised animals had lower DNA fragmentation. Finally, physical exercise preserved pro-opiomelanocortin messenger RNA content. In conclusion, exercise training was able to reorganize the control of the energy balance through anti-inflammatory and antiapoptotic responses in hypothalamic tissue of obese mice.
Keywords: apoptosis; exercise; food intake; hypothalamus; obesity